Exploring Intercultural Capability on Indonesian Teachers of English: A Narrative Study - Lazuar Azmi Zulferdi; Nudia Imarotul Husna (JEELS (Journal of English Education and Linguistics Studies), 2022)
This paper presents a study on the development of Indonesian English as a Foreign Language (EFL) teachers’ intercultural capability in an overseas study program and its impacts on classroom English Language teaching practices. By using narrative inquiry as a research methodology, this study draws on the stories of two Indonesian EFL teachers’ experiences of intercultural learning during the master's degree program overseas. Data were gathered through semi-structured individual interviews with Indonesian EFL teachers who have completed Master of Teaching English to Speakers of Other Languages (TESOL) studies in Australia. Findings show that communication and cultural disequilibrium in an overseas study program plays a crucial role in the development of EFL teachers’ intercultural capability to enable them to develop their attributes from ethnocentrism to ethnorelativism. The findings also reveal that although the teachers become interculturally capable, the overseas study program does not necessarily contribute to their oral English skill development. As a further result, this study reveals that the development of the teachers’ intercultural capability affects their subsequent classroom English teaching practices in a way that they begin to employ dialogical communication and interaction by reflecting on their past experiences.